The Effects of Ownership Concentration, Company Size, and Profitability on Internet Financial Reporting - Tri Utami Lestari; Muhammad Nur Fauzi (Yayasan Ilomata, 2023)
As we have entered the digital age, a shift has occurred in which the internet has considerably become a significant aspect in all sectors. Not only individuals but also organizations use internet for a number of purposes. Internet financial reporting (IFR) is a company web-based information provided to stakeholders with the aim of disclosing information and minimizing information gaps. The data in this study are taken from the energy company listed in the Indonesian Stock Exchange (IDX). The objective of this study was to analyze the effects of ownership concentration, company size, and profitability on IFR using purposive sampling technique, generated from the total of 144 samples comprising 48 companies with a period of 3 years. The regression method in this study uses panel data regression. The results indicate that ownership concentration, company size, and profitability simultaneously affect IFR. Partially, independent variable company size positively and significantly affect internet financial reporting, while ownership concentration and profitability do not affect IFR as the dependent variable.